Openness and economic efficiency: evidence from the Chilean manufacturing industry - Fuentes, Rodrigo (Estudios de Economía, 2016)
This paper highlights a long-standing debate on whether openness does help economic efficiency in the light of the data for Chilean manufacturing industry. To do so, we analyse the TFP growth during the period of the abrupt trade reform in the seventies. This data base provides evidence favoring the hypothesis that a shift towards a condition of laissez faire substantially improves productivity in the economy. In actual fact, during the period 1975 – 1979, the annual rate of TFP growth in the manufacturing industry was 4.35 percent yearly on average. However, for the period 1980 – 1982 this growth was -0.67. The sectors whose productivity increased at a greater speed, in the first years of the reform, were those associated with natural competitive advantages. Subsequently an increase in those industries which are more capital intensive was recorded. This contrasts with some results which were obtained earlier and confirms others which are addressed in the paper.